FACTORS CAUSING READING COMPREHENSION DIFFICULTIES AMONG THE SEVENTH GRADERS - M. Wahyu Ibrahim; Umar Abdullah; Hariana Amalia (IKIP Siliwangi, 2024)
The purpose of this study was to explore the factors causing reading comprehension difficulties. This study used a qualitative method with a case study research design to describe the factors causing reading comprehension difficulties among the seventh grade students in Palembang. The data were collected through structured interviews with four students and analyzed thematically. The study found five factors contributing to students' difficulties in reading comprehension, including problems with understanding long sentences, the use of poor reading strategies, lack of concentration, house environment, and school environment. This study provided suggestions for teachers and students. Teachers should use creative teaching methods and emphasize the development of all four language skills to make learning more interesting. Students should improve their English by enriching their vocabulary, using effective reading comprehension strategies, and seeking support from parents.